INNOVATIONS IN HUMAN RESOURCE MANAGEMENT: GERMAN PRACTICES IN MIGRANT INTEGRATION AND REDUCED WORKWEEK EXPERIMENTS - Kotykova, Olena; Babych , Mykola; Babych , Bohdan (АКТУАЛЬНІ ПРОБЛЕМИ МЕНЕДЖМЕНТУ ТА ПУБЛІЧНОГО УПРАВЛІННЯ В УМОВАХ СУЧАСНИХ ВИКЛИКІВ, 2025)
.